Opportunities for multiscale computational modelling of serotonergic drug effects in Alzheimer's disease. (1st September 2020) - Joshi, Alok; Wang, Da-Hui; Watterson, Steven; McClean, Paula L.; Behera, Chandan K.; Sharp, Trevor; Wong-Lin, KongFatt
Abstract: Alzheimer's disease (AD) is an age-specific neurodegenerative disease that compromises cognitive functioning and impacts the quality of life of an individual. Pathologically, AD is characterised by abnormal accumulation of beta-amyloid (Aβ) and hyperphosphorylated tau protein. Despite research advances over the last few decades, there is currently still no cure for AD. Although, medications are available to control some behavioural symptoms and slow the disease's progression, most prescribed medications are based on cholinesterase inhibitors. Over the last decade, there has been increased attention towards novel drugs, targeting alternative neurotransmitter pathways, particularly those targeting serotonergic (5-HT) system. In this review, we focused on 5-HT receptor (5-HTR) mediated signalling and drugs that target these receptors. These pathways regulate key proteins and kinases such as GSK-3 that are associated with abnormal levels of Aβ and tau in AD. We then review computational studies related to 5-HT signalling pathways with the potential for providing deeper understanding of AD pathologies. In particular, we suggest that multiscale and multilevel modelling approaches could potentially provide new insights into AD mechanisms, and towards discovering novel 5-HTR based therapeutic targets. Highlights: Alzheimer's disease (AD) drug treatment is limited, and alternatives are needed. Serotonin (5-HT) mediated signalling pathways may regulate Aβ and tau levels. 5-HT based drugs have the potential to provide as novel therapeutics for AD. Complex 5-HT signalling mechanisms for AD and related drugs hinder understanding. Multiscale models may offer insights into mechanisms and therapeutic targets.